Catastro y caracterización de las fuentes fijas de contaminación industrial, agroindustrial y de servicios del cantón Latacunga, provincia de Cotopaxi - Vela Alarcón, Guillermo Pablo (2012)
The present investigation work has the environmental problem analysis caused by the contamination fixed sources or subject of control located in the Canton Latacunga; besides justification based on social axles, productive and environmental they constitute the reason of the environmental investigation. The general and specific objectives determine the steps to follow the structure of the investigation search named Cadaster and Characterization of the Fuentes Fixed of Industrial, Agroindustrial Contamination and of Services of the Latacunga Canton from Cotopaxi County. The thematic describe conceptualizations and definitions of processes of contamination and types of pollutants; as well it determines criterions of classification of contamination sources and services, being constituted in the theoretical frame of this investigation work....